Mecanismos envolvidos na indução de morte celular por desacetilnemorona em células de câncer colorretal - Araújo, Ana Jérsia (2013)
The desacetylnemorone (HCRH) is an abietane diterpene with para-quinone ring in its structure, and then classified as a tanshinone that are often described by their broad spectrum of biological activities. The diterpene HCRH was isolated and identified for the first time in 1971 from roots of plants of the genus Salvia, however its biological activity has not been yet fully characterized. The aim of this study was to evaluate the anticancer potential of desacetylnemorone isolated from the roots of the plant Hyptis carvalhoi. The present study evaluated the cytotoxic potential of the diterpene HCRH in several tumor and normal cell lines using the MTT assay and its possible mechanism of action. After 72 hours of incubation, the tested compound showed IC50 values ranging from 3.91 to 32.01 µM in colon tumor (HCT-116) and leukemic (HL-60) cells, respectively. While for normal cells IC50 values ranged from 35.68 µM in V-79 to higher than 72 µM in 3T3-L1 and PBMC cells. In colon tumor cells (HCT-116), the diterpene showed antiproliferative potential of time-dependent manner, leading to increased number of cells in the G0/G1 phase of the cell cycle and a substantial decrease in DNA synthesis. These effects were accompanied by changes in the levels of cyclins and CDKs, in addition to the increase in the levels of proteins p21waf1/cip1 and p27kip1, independent of p53 activation. Among the initial events induced by diterpene HCRH are the generation of reactive oxygen species (ROS) and the induction of DNA damage with subsequent activation of death pathways. Thus, we can suggest that desacetylnemorone has potent antiproliferative activity associated with ROS generation leading to DNA damage, which prevents cell cycle progression and drive cells to the process of death by apoptosis and autophagy.